Utilization of organic soil amendments and phosphorus fertilizer to improve chemical properties of degraded dry land Vertisol and maize yield - Rupa Matheus; Donatus Kantur; Maria K Salli (Journal of Degraded and Mining Lands Management, 2023)
This study aimed to evaluate the effects of soil amendment and phosphorus fertilizer application techniques on the chemical properties of dry land Vertisols, P absorption efficiency by maize and maize yield. The study was conducted on farmer's land located in Noelbaki Village, Central Kupang District, Kupang Regency, East Nusa Tenggara, Indonesia. The study was conducted during two planting seasons, namely the rainy season 2020/2021 (PS-1) and the dry season 2021 (PS-2). The soil used in this experiment was included in the degraded Vertisols. This study used a split-plot design with three replications. The main plot was the type of organic soil-amendment material, and the subplot was the technique (dose and stage) of applying phosphorus fertilizer sourced from SP-36. The results showed that organic soil amendment and phosphorus fertilizer application techniques could improve soil chemical properties, P uptake, P absorption efficiency and maize yield in Vertisols until the second planting season. In the long term, the combination of maize stover biochar and the technique of applying phosphorus fertilizer (P3-T2) significantly increased the P uptake by 32.31 kg ha-1 (PS-1) and 31.23 kg ha-1 (PS-2), the P absorption efficiency by 28.65% (PS-1) and 27.75% (PS-2). The P3-T2 treatment gave maize yields of 6.92 t ha-1 (PS-1) and 6.92 t ha-1 (PS-2), which were higher than those of other treatments.